Four Ethical Issues of the Information Age - Mason, Richard O.; Collins, Carr P.; Cox, Edwin L. (MIS Quarterly, 1986)
In western societies more people are employed collecting, handling and distributing information than in any other occupation. Millions of computers inhabit the earth and many millions of miles of optical fiber, wire and air waves link people, their computers and the vast array of information handling devices together. There are many unique challenges we face in this age of information. They stem from the nature of information itself. Information is the means through which the mind expands and increases its capacity to achieve its goals, often as the result of an input from another mind. Two forces threaten our privacy. One is the growth of information technology, with its enhanced capacity for surveillance, communication, computation, storage, and retrieval. A second, and more insidious threat, is the increased value of information in decisionmaking. Collections of information reveal intimate details about a person and can thereby deprive the person of the opportunity to form certain professional and personal relationships.